Student Digital Divide Due to Geographic Conditions Among Rural Communities - Roly Edyan; Tengku Ahmad Fauzansyah; Aditya Ly (Universitas Batanghari Jambi, 2026)
The development of information and communication technology in the current century has provided extraordinary changes in various sectors, including the field of education. The integration of technology in education, especially in primary and secondary schools, is an important issue to improve the quality of learning and enrich the learning experience of students. Lifuleo Village, Kupang Regency, NTT is one of the areas in the archipelago and is on the outskirts of Kupang city which has challenges in digital usage. The aim of this research is to reveal what factors cause digital inequality in Lifuleo Village, Kupang Regency, NTT. This research is a type of qualitative research using interview methods and direct observation in the field. The results of this research conclude that the influence of the digital divide is due to the hilly geographical conditions in Lifuleo village, Kupang Regency, NTT, lack of information and communication infrastructure in the Lifuleo area, low internet speed which hinders access to learning materials, costs for internet access are very high.